Ответы и объяснения

2012-11-19T12:39:36+00:00

\frac{(-6x^2+6x+36)(2x^2+3x-5) }{(x-4)(x-1)}>=0\\ \frac{(-x^2+x+6)(2x^2+3x-5) }{(x-4)(x-1)}>=0\\ \frac{(-x^2+x+6)(x^2+1,5x-2,5) }{(x-4)(x-1)}>=0\\ \frac{-(x^2-x-6)(x+2,5)(x-1) }{(x-4)(x-1)}>=0\\ \frac{-(x-3)(x+2)(x+2,5)(x-1) }{(x-4)(x-1)}>=0\\  

Обе части на -1:

 \frac{(x-3)(x+2)(x+2,5)(x-1) }{(x-4)(x-1)}<=0\\\begin{cases} x=3\\x=-2\\x=-2.5\\ x=1\\x\neq 1\\x \neq4 \end{cases}

 

Во всех точках ф-ия будет менять знак, за искл. x=1

 

         -2,5         -2                1            3              4

--------\----------\-------------\----------\------------\----------x

     +          -              +             +                  -            +  

 

Ответ [-2,5;-2] [3;4)